The UCP2/PINK1/LC3b-mediated mitophagy is involved in the protection of NRG1 against myocardial ischemia/reperfusion injury - Xin-Tao Li; Xin-Yue Li; Tian Tian; Wen-He Yang; Shuai-Guo Lyv; Yi Cheng; Kai Su; Xi-Hua Lu; Mu Jin; Fu-Shan Xue (Redox Biology)
Available evidence indicates that neuregulin-1 (NRG-1) can provide a protection against myocardial ischemia/reperfusion (I/R) injury and is involved in various cardioprotective interventions by potential regulation of mitophagy. However, the molecular mechanisms linking NRG-1 and mitophagy remain to be clarified. In this study, both an in vivo myocardial I/R injury model of rats and an in vitro hypoxia/reoxygenation (H/R) model of H9C2 cardiomyocytes were applied to determine whether NRG-1 postconditioning attenuated myocardial I/R injury through the regulation of mitophagy and to explore the underlying mechanisms. In the in vivo experiment, cardioprotective effects of NRG-1 were determined by infarct size, cardiac enzyme and histopathologic examinations. The potential downstream signaling pathways and molecular targets of NRG-1 were screened by the RNA sequencing and the Protein-Protein Interaction Networks. The expression levels of mitochondrial uncoupling protein 2 (UCP2) and mitophagy-related proteins in both the I/R myocardium and H/R cardiomyocytes were measured by immunofluorescence staining and Western blots. The activation of mitophagy was observed with transmission electron microscopy and JC-1 staining. The KEGG and GSEA analyses showed that the mitophagy-related signaling pathways were enriched in the I/R myocardium treated with NRG-1, and UCP2 exhibited a significant correlation between mitophagy and interaction with PINK1. Meanwhile, the treatment with mitophagy inhibitor Mdivi-1 significant eliminated the cardioprotective effects of NRG-1 postconditioning in vivo, and the challenge with UCP2 inhibitor genipin could also attenuate the activating effect of NRG-1 postconditioning on mitophagy. Consistently, the in vitro experiment using H9C2 cardiomyocytes showd that NRG-1 treatment significantly up-regulated the expression levels of UCP2 and mitophagy-related proteins, and activated the mitophagy, whereas the challenge with small interfering RNA-mediated UCP2 knockdown abolished the effects of NRG-1. Thus, it is conclused that NRG-1 postconditioning can produce a protection against the myocardial I/R injury by activating mitophagy through the UCP2/PINK1/LC3B signaling pathway.